2020
DOI: 10.21203/rs.2.20785/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncolytic vaccinia virus GLV-1h68 exhibits profound antitumoral activities in cell lines originating from neuroendocrine neoplasms

Abstract: Background: Oncolytic virotherapy is an upcoming treatment option for many tumor entities. But so far, a first oncolytic virus only was approved for advanced stages of malignant melanomas. Neuroendocrine tumors (NETs) constitute a heterogenous group of tumors arising from the neuroendocrine system at diverse anatomic sites. Due to often slow growth rates and (in most cases) endocrine non-functionality, NETs are often detected only in a progressed metastatic situation, where therapy options are still severely l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Susceptibility to GLV-1 h68 treatment was found to be dose-dependent. Comparing these results to other OVs already tested in NENs, GLV-1 h68 showed favorable cytotoxicity for pan-NETs and NECs [113]. The oHSV T-VEC was found to be particularly effective in lung and pan-NETs previously.…”
Section: Ovs and Gep-nensmentioning
confidence: 51%
See 3 more Smart Citations
“…Susceptibility to GLV-1 h68 treatment was found to be dose-dependent. Comparing these results to other OVs already tested in NENs, GLV-1 h68 showed favorable cytotoxicity for pan-NETs and NECs [113]. The oHSV T-VEC was found to be particularly effective in lung and pan-NETs previously.…”
Section: Ovs and Gep-nensmentioning
confidence: 51%
“…GLV-1 h68 showed favorable cytotoxicity for pan-NETs and NECs [113]. The oHSV T-VEC was found to be particularly effective in lung and pan-NETs previously.…”
Section: Development Of Oncolytic Vacv Glv-1h68 For Gep-nensmentioning
confidence: 90%
See 2 more Smart Citations
“…It was found that GLV-1 h68 is able to infect and reduce tumor cell masses in six NET and NEC cell lines in a dose-dependent manner. High titers of extracellular viral payload were observed [91].…”
Section: Oncolytic Virus or Virotherapymentioning
confidence: 99%